Analisis Keuntungan Usaha Penggilingan Padi Di Desa Poopo Barat Kecamatan Ranoyapo Kabupaten Minahasa Selatan - Soputan, Lavenda; Kaunang, Rine; Rori, Yolanda Pinky Ivanna (Sam Ratulangi University, 2023)
The objective of this research is to analyze the profit from the rice milling business West Poopo Village, Ranoyapo District, South Minahasa Regency. This research was conducted from April to June 2023. The data used in this research are primary data and secondary data. Primary data were obtained from direct interviews with rice mill business owners. Secondary data were obtained from the Village Office, the Central Bureau of Statistics and other sources related to research. The sampling technique in this study used the Non-Probability Sampling method with purposive sampling. The data analysis method used is descriptive analysis which will be presented in tabular form. The research results obtained showed that the rice mill business in Poopo Barat Village, Ranoyapo District was profitable, both during the harvest season and not during the harvest season. The profit earned during the harvest season is IDR10.096.287 and during the non-harvest season is IDR2.385.286. The average profit within one month is IDR1.040.131.